2007
DOI: 10.1007/s00540-006-0477-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sonoclot hemostasis analysis after cardiopulmonary bypass on postoperative hemorrhage in cardiac surgery

Abstract: Our results suggest that abnormal postoperative hemorrhage can be predicted by Sonoclot analysis with a new glass bead-activated heparinase test performed after CPB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…A slightly different principle is embodied in the Sonoclot instruments, in that the viscoelastic probe vibrates vertically, 118 and the shape of the trace is somewhat different, producing a 'signature' with various peaks 106,[125][126][127] (Fig. 5).…”
Section: Thromboelastography Thromboelastometry and Sonoclot Instrummentioning
confidence: 99%
“…A slightly different principle is embodied in the Sonoclot instruments, in that the viscoelastic probe vibrates vertically, 118 and the shape of the trace is somewhat different, producing a 'signature' with various peaks 106,[125][126][127] (Fig. 5).…”
Section: Thromboelastography Thromboelastometry and Sonoclot Instrummentioning
confidence: 99%
“…In contrast, in critically ill humans receiving enoxaparin TEG R‐times differed significantly between patients that experienced a deep vein thrombosis and those that did not while anti‐factor Xa activity was similar between the 2 groups suggesting that TEG rather than anti‐factor Xa activity might be the more appropriate monitoring technique . There is less information about the utility of the Sonoclot analyzer; however, Sonoclot ACT has a similar reliability and accuracy when compared to established measures of coagulation and Sonoclot analysis has utility in the prediction of hemorrhage following cardiopulmonary bypass surgery …”
Section: Discussionmentioning
confidence: 99%
“…Although this assay has been used to measure anti‐factor Xa activity in horses, it is relatively expensive and not available in most veterinary hospitals. Thromboelastography (TEG) and Sonoclot are point‐of‐care viscoelastic coagulation tests that provide real time measures of the rate of clot formation and clot strength and have been evaluated for monitoring anticoagulant therapy in select human hospital populations . TEG and Sonoclot are becoming more widely available in veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Fondaparinux is a new anticoagulant that interacts with antithrombin III and activated coagulation factor X resulting in an inhibition of the coagulation system. It has been concluded that the Sonoclot parameter clot rate could be of clinical value to individualize the fondaparinux dosage, especially the higher, therapeutic, dosages [8].…”
Section: Introductionmentioning
confidence: 99%